The Accuracy of Referral for Portable Lipid Analyzers in an Old Order Mennonite Population - Maria Eve Main; Susan Jones; Cathy Abell (Rural Nurse Organization; Binghamton University, 2010)
The primary purposes of this study were to: 1) examine the accuracy for referral of two portable lipid analyzers (PLAs) in an old order Mennonite population through a comparison to a national standardized reference laboratory, 2) examine the relationship of total cholesterol values with other known cardiovascular risk factors, and 3) foster the continued participatory model of health care service in this community. The self-selected sample was composed of 42 adult members of an old order Mennonite community residing in south central Kentucky. A descriptive correlational design was used in this study. There were clinically relevant variations in the total cholesterol and LDL-C in both of the analyzers. Additionally, there was a correlation between total cholesterol values and age. The study also facilitated the participatory model used with this community previously as the community members assisted in planning, implementing, and evaluating this project.